SOSIALISASI MOBILE DOCTOR UNTUK MENINGKATKAN LAYANAN MEDIS BAGI MASYARAKAT DI DESA WUKIRSARI KECAMATAN IMOGIRI KABUPATEN BANTUL - Gatot Santoso; Slamet Hani (JURNAL GAUNG INFORMATIKA, 2017)
A university is present in the community to assume the function of Tri Dharma Perguruan Tinggi, which is the function of Education and Teaching, Research, and Community Service. In order for Universities to be in direct contact with the communitythrough the practice of science and technology, then the activities of community service must be done. Program of Community Service (Abdimas) is not only done by lecturers, but also students who are concrete tangible Real Work Lecture (KKN).KKN program at the Institute of Science & Technology AKPRIND Yogyakarta, as well as efforts to improve empathy and awareness of students in the community and apply science, especially science and technology in the midst of society. The process of implementing this KKN also get guidance from lecturers. In the guidance of this KKN, lecturers also play a role in the implementation of community service. With the involvement of this lecturer is expected to implement KKN can run in accordance with the policy of the Institute. As the implementation of community service, especially at the location of KKN Wukirsari Bantul District, KKN team and lecturers provide science and technology themed training. The training provided includes a mobile doctor targeted at the community.